Experimental evaluation of predictive voltage control for a four‐leg two‐stage matrix converter. Issue 12 (13th September 2019) - Garcia, Cristian; Rivera, Marco; Rodriguez, Jose; Wheeler, Pat
Abstract : Model predictive control (MPC) has emerged as a real alternative for the control of different topologies of power converters. In particular, MPC has been successfully applied in matrix converters, significantly reducing the difficulty of control compared with classical techniques. In this study, a predictive voltage control strategy for a four‐leg indirect matrix converter is proposed. The idea is based on the discrete minimisation of a cost function in order to select the best vector state of the power converter to be applied in the next sampling instant. Experimental results are presented to validate the proposal under several operating points.